Pendidikan Pancasila sebagai wahana Pendidikan Politik di organisasi kesiswaan - Dhea Marchelia; Al Rafni; Suryanef Suryanef; Hasrul Hasrul (Journal of Education, Cultural and Politics, 2026)
Pancasila Education plays a strategic role as a vehicle for political education in shaping democratic attitudes and enhancing student participation within the school environment. This study aims to analyze how Pancasila Education contributes to fostering democratic attitudes and student participation in school organizations, specifically the Student Council (OSIS) at SMAN 1 Batusangkar. The method used is a descriptive qualitative approach through observation, interviews, and a preliminary survey of students active in the organization. The results of the study indicate that although students have understood the concept of democracy theoretically, its implementation in organizational activities remains suboptimal. This is evident from the dominance of the core executive members in decision-making, students’ participation that tends to be passive, and members’ involvement that is still limited to the implementation stage of activities. This situation indicates that democratic values have not yet been fully internalized in organizational practices. Therefore, more contextual learning innovations and evaluations that focus not only on cognitive aspects but also on affective and psychomotor aspects are needed so that Pancasila Education can function more effectively as political education.